2015
DOI: 10.14710/ik.ijms.20.3.121-126
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons (PAHs) in Muscles of Two Commercial Fish Species from Al-Kahlaa River in Missan Governorate, Iraq

Abstract: Al-Kahlaa River is one of main tributaries of the Tigris River in Missan city and rises from northwest side of Amara city and continues to flow in the direction to the east of city center. Two commercial fish species (Liza abu andCarassius auratus) were collected seasonally (autumn, winter, spring and summer)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…High temperature also stimulate microorganisms to break down these compounds, especially low molecular weights of PAHs (11), and the process of optical oxidation is even greater because of the length of the day and intensity of brightness of solar radiation(4). The results of present study are in agreement with Jazza et al (16)who recorded that the higher concentrations of PAHs in winter, whereas the lower concentrations in summer at Al-Kahlaa River in Missan Province, Iraq. Also these findings in agreement with Al-Hijaj et al(3)who reported that the highest concentration of PAH compounds in water was 31.254 mg/l during winter and the lowest concentration was 3.62 mg/l during summer at northern part of Shatt-Al-Arab River, Iraq.…”
Section: Total Concentration Of Pahs In Watersupporting
confidence: 93%
See 1 more Smart Citation
“…High temperature also stimulate microorganisms to break down these compounds, especially low molecular weights of PAHs (11), and the process of optical oxidation is even greater because of the length of the day and intensity of brightness of solar radiation(4). The results of present study are in agreement with Jazza et al (16)who recorded that the higher concentrations of PAHs in winter, whereas the lower concentrations in summer at Al-Kahlaa River in Missan Province, Iraq. Also these findings in agreement with Al-Hijaj et al(3)who reported that the highest concentration of PAH compounds in water was 31.254 mg/l during winter and the lowest concentration was 3.62 mg/l during summer at northern part of Shatt-Al-Arab River, Iraq.…”
Section: Total Concentration Of Pahs In Watersupporting
confidence: 93%
“…Shabout Arabibarbus grypus is a species that can be founded in Rivers also can be founded in estuaries, getting a maximum size of approximately two meters and more than 50kg(20), is belonging to euryhaline and eurytherme species , nutritionally omnivorous and extensively spread in Iran, Turkey, Syria and Iraq (10). Hydrocarbon compounds such as naphthalene, acenaphthylene, acenaphthene, fluorine, phenanthrene, anthracene, fluoranthene, pyrene, benz (a)anthracene, chrysene, benzo (b) fluoranthene, benzo(k)fluoranthene, benzo (a) pyrene, benzo (ghi) perylene dibenz (a,h)anthracene and indeno(1,2,3-cd)pyrene .These compounds enter to fish tissues either during direct contact ,contaminate their gills or via food contamination, also PAHs and their intermediate degradation products have the potential to generate toxic or mutagenic effects in fish (16) and humans (21). Reaching higher levels in Rivers ,therefore this can affect human health in areas that have commercial fisheries (21).…”
Section: Introductionmentioning
confidence: 99%
“…The level of PAHs (104 and 76.5 µg/kg) reported for total PAHs in the fresh and smoked fish extracts from the present study were comparatively lower than those reported for Periophthalamus koeleuteri (172 µg/kg), Crassostrea virginica (105 µg/kg) [34]; higher than M. undulatus (9.4 -17.7 µg/kg), O. niloticus (12.6 -18.7 µg/kg) and S. lalandi (16.1 -20.2 µg/kg) [35], Liza abu (2.30 -16.7 µg/kg), Carassius auratus (1.09 -8.67 µg/kg) [36], while Crassostrea virginica (97.2 -105 µg/kg) [23] from Kpoghor and Iko showed a similar trend. In the comparison of the dry extract concentration from the smoked and fresh samples in the groups of the head, liver, and muscles (Tables 2 -4), the head, liver, and muscle all showed build up values in the TPAH, total non-carcinogenic PAHs, and total high molecular PAHs after smoking.…”
Section: Resultsmentioning
confidence: 90%